Sistema de Avaliação Nacional: impacto sobre as instituições privadas: estudo de caso do Centro Universitário FUMEC - Guimarães, Maria Helena de Oliveira (2002)
The aim of this paper is evaluate the impacts that the National Evaluation System - NES, implanted by the federal government in 1996 from the law n. 9.131/95 is provoking in the college education system. After an expansion foccused just in trach, this institutions had to redefine their goals searching a better quality offer in graduation courses due to pressure of the academic community and the society. The national education System proposes, for the first time in the Brazilian superior education, that the quality of the graduation courses, the public or private third degree institutions have evaluated in a periodic and systematic way- the main instruments to this evaluation are the National course Exam, knowon by "Provào" and the Evaluation Commissions of the courses offer conditions and institutional evaluation. The study foccused their analyses at the FUMEC Universitary Center in Belo Horizonte/MG, as a non universitary institution at the market from 36 years that is passing throw important changes trying to adapt the defined quality pattern to the graduation courses according to the evaluation system. To evaluate the impacts of the National Evaluation System a research was made in how and which grade FUMEC's teachers and students notice the course and institution changes after submiting to NES, in the last 5 years.